Challenges faced by bilingual stroke survivors in the healthcare system: Unique considerations - Sauvé-Schenk, Katrine; Dubouloz-Wilner, Claire-Jehanne; Egan, Mary; Kristjansson, Elizabeth (Linguistic Minorities and Society, 2020)
The experiences of multilingual patients communicating with unilingual healthcare providers have been largely unexplored. The aim of this study was to investigate the experiences of bilingual stroke patients within the Canadian healthcare context. A secondary analysis was completed with data from a multiple case study of the experiences of seven, low-income bilingual Francophone stroke survivors living in a predominately English area. Data included semi-structured interviews, chart reviews and language proficiency assessments. Results demonstrated that bilingual survivors experience unique challenges, including limited French health vocabulary, use of non-standard French, and generally low health literacy levels in both languages. Participants with aphasia often used English and French interchangeably, leading to the potential for miscommunication when providers were not bilingual. The study highlights the importance of having bilingual healthcare providers when bilingual stroke survivors have communication or cognitive limitations. Keywords: Stroke, language, bilingualism, healthcare, literacy

L’accès aux services en français, de la connaissance des défis à l’accompagnement des organisations vers le changement. - Savard, Sébastien; Savard, Jacinthe; Sauvé-Schenk, Katrine; van Kemenade, Solange; Benoît, Josée (Minorités linguistiques et société, 2024)
Depuis 2011, le Groupe de recherche sur la formation et les pratiques en santé et service social en contexte francophone minoritaire (GReFoPS) cherche à mieux comprendre les facilitateurs et les obstacles à l’offre de services en français dans un contexte linguistique minoritaire au Canada. Dans cet article, les auteurs présentent un bilan de près de 12 ans de recherche sur le sujet, en décrivant les facteurs individuels et organisationnels qui influencent l’offre de services en français. Les résultats de ces études ont mis en lumière quelques mécanismes organisationnels ou interorganisationnels qui ont permis l’émergence de pratiques novatrices pour améliorer l’offre de services en français dans les services communautaires et institutionnels. On y décrit également des outils créés pour aider les gestionnaires de ces services à identifier des mesures et des mécanismes pouvant répondre aux besoins des usagers francophones en situation minoritaire. Mots-clés : accès, services sociaux et de santé, francophones, contexte minoritaire, Canada

Conditions gagnantes pour une offre active de services en français efficace dans un milieu à faible densité de francophones : résultats d’une étude pilote. Rapport sommaire présenté à la Société Santé en français - Sauvé-Schenk, Katrine; Savard, Jacinthe; Prud’homme, Denis; Durand (Chiocchio), F.; Delluc, C. (Institut du savoir Montfort et Groupe de recherche sur la formation et les pratiques en santé et service social en contexte francophone minoritaire, 2021)

Active offer of services in Canada’s official languages: development of a patient experience questionnaire - Sauvé-Schenk, Katrine; Pignac, Sarah; Kemenade, Solange Van; Savard, Sébastien; Prud'homme, Denis; Savard, Jacinthe (Journal of Communication in Healthcare, 2026)
ABSTRACT Background: In the bilingual Canadian context, the use of a preferred official language with healthcare providers is linked to optimized communication, respectful patient-centered care, improved safety and quality of services. This study aimed to develop and test a questionnaire that measures patients’ experience of how language was considered during an outpatient health encounter. Methods: French and English questions were drafted based on a literature review. Questionnaire content and flow were validated through focus groups with experts and service users. Question understanding and clarity was verified with cognitive interviews and pre-tests with diverse service users. The final questionnaire was pilot tested in three health organizations and temporal stability, and construct validity was verified. Results: Participants were nine anglophone and eleven francophone experts and service users for the focus groups, six anglophone and six francophone service users for the cognitive interviews, eleven anglophone and ten francophone service users for the pre-test. The resulting questionnaire has 31 experience-related questions organized under six themes: arrival/greeting, interpretation and translation services, language of health services, relationship with healthcare providers, visibility of official languages and follow-up. The questionnaire is completed online in French or English. The questionnaire was pilot tested with 199 participants in three sites. Temporal stability was moderate to good. Initial evidence of construct validity was demonstrated, suggesting that the questionnaire is adequate to evaluate patient experience. Conclusion: This questionnaire is the first known bilingual patient-experience tool, focused on the active offer of services in official languages during outpatient healthcare encounters, with preliminary validation.